2022
DOI: 10.3390/foods11223600
|View full text |Cite
|
Sign up to set email alerts
|

Dietary DHA Enhanced the Textural Firmness of Common Carp (Cyprinus carpio L.) Fed Plant-Derived Diets through Restraining FoxO1 Pathways

Abstract: Omega-3 fatty acids have a positive effect on the muscle textural firmness of fish, while the intrinsic mechanism is poorly understood. To investigate the potential mechanism of textural modification caused by dietary docosahexaenoic acid ( DHA) in common carp (Cyprinus carpio L.), three plant-derived diets with varying DHA levels (0%, 0.5%, 1%, D1–D3) were prepared to feed juveniles (initial weight 15.27 ± 0.77 g) for 8 weeks, and the muscular texture, fibers density, and transcriptome were analyzed. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…Feeding of 0.8% DHA for 56 days significantly increased muscle hardness, gumminess, and chewiness in blunt snout bream, which was partially associated with stimulated myocyte hyperplasia and increased sarcomere lengths 150 . Similar results were observed in common carp, where dietary 0.5–1.0% DHA significantly increased flesh hardness, fibre density, and sarcomere length but caused decreased fibre diameter 151 . The data of transcriptome along with qPCR indicated that DHA supplementation activated Mrfs family (including mrf4 , mrf5 , myog , and myod ), probably mediated by restraining FoxO1 pathways in the muscle.…”
Section: Strategies To Regulate Texture Characteristics In Aquaculturesupporting
confidence: 63%
“…Feeding of 0.8% DHA for 56 days significantly increased muscle hardness, gumminess, and chewiness in blunt snout bream, which was partially associated with stimulated myocyte hyperplasia and increased sarcomere lengths 150 . Similar results were observed in common carp, where dietary 0.5–1.0% DHA significantly increased flesh hardness, fibre density, and sarcomere length but caused decreased fibre diameter 151 . The data of transcriptome along with qPCR indicated that DHA supplementation activated Mrfs family (including mrf4 , mrf5 , myog , and myod ), probably mediated by restraining FoxO1 pathways in the muscle.…”
Section: Strategies To Regulate Texture Characteristics In Aquaculturesupporting
confidence: 63%